Microstructure analysis of cement pastes and high-strength concrete incorporated diatomaceous earth damaged due to Na2SO4 attack - Aprilia Yella; Hasan Muttaqin; Abdullah, Mahlil Nora; Saidi Taufiq (E3S Web of Conferences)
Diatomaceous earth can be an alternative to replace cement in concrete production partially. This study focuses on investigating and evaluating the microstructure of high-strength concrete (HSC) mixtures involving 15% diatomaceous earth (DE) as cement replacement and cement paste involving 20% DE after exposure to sodium sulfate (Na2SO4) effects. HSC and cement paste mixtures without using DE were used as references. The test specimens are cubes of 50 mm x 50 mm x 50 mm, which are immersed in a 10% Na2SO4 solution for 4 months after reaching the age of 28 days. Observations of microstructures were conducted using scanning electron microscopy (SEM). The SEM results indicate the addition of DE enhances the formation of a cement hydration matrix in the form of C-S-H, which can improve resistance to sulfate attack. Under similar conditions, concrete without diatomaceous earth shows a more significant formation of ettringite, especially by sulfate solution.